2023
DOI: 10.3390/biology12060779
|View full text |Cite
|
Sign up to set email alerts
|

Compatible Consortium of Endophytic Bacillus halotolerans Strains Cal.l.30 and Cal.f.4 Promotes Plant Growth and Induces Systemic Resistance against Botrytis cinerea

Abstract: Evaluating microbial-based alternatives to conventional fungicides and biofertilizers enables us to gain a deeper understanding of the biocontrol and plant growth-promoting activities. Two genetically distinct Bacillus halotolerans strains (Cal.l.30, Cal.f.4) were evaluated for the levels of their compatibility. They were applied individually or in combination under in vitro and greenhouse conditions, using seed bio-priming and soil drenching as inoculum delivery systems, for their plant growth-promoting effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Similar findings were observed by Kumar et al [ 98 ], who suggested that microbial consortiums of B. subtilis OTPB 1 and T. harzianum OTPB 3 coated tomato seeds showed elevated plant growth and induction of systemic resistance compared to their single-treatment counterparts. Recent studies conducted by Tsalgatidou et al [ 99 ] reported that tomato seed biopriming with a combination of Bacillus halotolerans (Cal.l.30 and Cal.l.4) gave better results in plant growth promotion parameters such as shoot and root length and plant biomass compared to untreated plants under pathogen-challenged conditions. In another investigation, the combined treatment of P. gessardi EU-LWNA-25, Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed by Kumar et al [ 98 ], who suggested that microbial consortiums of B. subtilis OTPB 1 and T. harzianum OTPB 3 coated tomato seeds showed elevated plant growth and induction of systemic resistance compared to their single-treatment counterparts. Recent studies conducted by Tsalgatidou et al [ 99 ] reported that tomato seed biopriming with a combination of Bacillus halotolerans (Cal.l.30 and Cal.l.4) gave better results in plant growth promotion parameters such as shoot and root length and plant biomass compared to untreated plants under pathogen-challenged conditions. In another investigation, the combined treatment of P. gessardi EU-LWNA-25, Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…rough the above evidence, it could be seen that the compatibility varies with each bacterial strain. e compatibility of antagonizing bacterial strains might enhance the ability to biocontrol phytopathogenic fungi, as reported by Palmieri et al (2016) and Tsalgatidou et al (2023). All of the four bacterial strains selected in this study were compatible, so they could form ideal combinations to be applied to control G. persicaria GTC2.3.1.…”
Section: Discussionmentioning
confidence: 56%
“…Bacterial characterization and their impact on tomato growth Among the characterized strains, it is worth noting the presence of Bacillus halotelarans that is a species harboring strains with growth promoting effects, as recently reported by Tsalgatidou et al (2023), and B. butanolivorans, which is known to be able to induce drought tolerance in pepper plants (Kim et al, 2022). A Peribacillus simplex strain was isolated from soil of tomato cultivation and, interestingly, this species has shown the capacity to accumulate lead and to have a biosorption potential (Chamekh et al, 2021).…”
Section: Discussionmentioning
confidence: 77%